2008
DOI: 10.1002/ccd.21375
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of coronary arterial flow‐mediated dilatation following percutaneous coronary intervention

Abstract: FMD occurs in human coronary arteries following restoration of flow. The magnitude of FMD appears related to vascular risk factors and their treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…The peak increase in arterial diameter is calculated (%FMD) and used as an index of systemic endothelial function [2, 3]. Impairment of endothelial function is central to the pathogenesis of atherosclerotic cardiovascular disease [4] and presence of cardiovascular risk factors is associated with attenuated brachial artery FMD [5,6,7] as well as coronary artery FMD [8]. …”
Section: Introductionmentioning
confidence: 99%
“…The peak increase in arterial diameter is calculated (%FMD) and used as an index of systemic endothelial function [2, 3]. Impairment of endothelial function is central to the pathogenesis of atherosclerotic cardiovascular disease [4] and presence of cardiovascular risk factors is associated with attenuated brachial artery FMD [5,6,7] as well as coronary artery FMD [8]. …”
Section: Introductionmentioning
confidence: 99%
“…The normal diameter of native coronary vessels can be underestimated in post-mortem and conventional invasive angiographic studies [11-14]. These studies usually assess only the mid-portion of the proximal segment of the coronary vessels rather than the ostium (the aorto-coronary junction), and report diameters of 2–5 mm for the RCA and 4–7 mm for the LMA.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that whilst conventional TTE failed to adequately assessed the coronary ostia of these patients, an alternative novel TTE acoustic window was able to visualize most of the coronary ostia, thus providing a potentially suitable alternative noninvasive imaging tool to monitor the coronary ostial dilation long-term. The normal diameter of native coronary vessels can be underestimated in post-mortem and conventional invasive angiographic studies [11][12][13][14]. These studies usually assess only the mid-portion of the proximal segment of the coronary vessels rather than the ostium (the aortocoronary junction), and report diameters of 2-5 mm for the RCA and 4-7 mm for the LMA.…”
Section: Discussionmentioning
confidence: 99%